2023
DOI: 10.3390/cells12121654
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Roles of the TRPV4 Channel in the Heart

Abstract: The transient receptor potential vanilloid 4 (TRPV4) channel is a non-selective cation channel that is mostly permeable to calcium (Ca2+), which participates in intracellular Ca2+ handling in cardiac cells. It is widely expressed through the body and is activated by a large spectrum of physicochemical stimuli, conferring it a role in a variety of sensorial and physiological functions. Within the cardiovascular system, TRPV4 expression is reported in cardiomyocytes, endothelial cells (ECs) and smooth muscle cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 183 publications
0
1
0
Order By: Relevance
“…Due to the two negatively charged aspartate residues within the conserved lower gate, it is easier for divalent ions than monovalent ions to pass through TRPV4. As a result, TRPV4 is mainly permeable to Ca 2+ rather than other ions, with the following permeability sequence: Ca 2+ >> Mg 2+ > K + > Na + , whereby the permeability for Ca 2+ is about five times higher than that of Mg 2+ , and about ten times higher than for Na + [46,47]. Four identical TRPV4 monomers form a functional channel.…”
Section: Protein and Channel Structure Of Trpv4mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the two negatively charged aspartate residues within the conserved lower gate, it is easier for divalent ions than monovalent ions to pass through TRPV4. As a result, TRPV4 is mainly permeable to Ca 2+ rather than other ions, with the following permeability sequence: Ca 2+ >> Mg 2+ > K + > Na + , whereby the permeability for Ca 2+ is about five times higher than that of Mg 2+ , and about ten times higher than for Na + [46,47]. Four identical TRPV4 monomers form a functional channel.…”
Section: Protein and Channel Structure Of Trpv4mentioning
confidence: 99%
“…TRPV4 mechanosensor is an integral factor in the progression of tissue repair and fibrotic disorders across different organs, including the skin, lungs, liver, kidneys, brain, blood vessels and heart [47]. In this section, we provide a comprehensive summary of the current understanding regarding the functions of TRPV4-induced Ca 2+ oscillation in each specific organ (Figure 4).…”
Section: Function Of Trpv4-evoked Ca 2+ Oscillations In Injury Repair...mentioning
confidence: 99%
“…DADLE could enhance the OGD/R-damaged cellular viability, elevate the mitochondrial membrane potential and promote ATP synthesis It has been reported that TRPV4 is expressed in endothelial cells and modulates mitochondrial activity. 17 DADLE offers neuroprotection against acute mitochondrial dysfunction. 18 Therefore, we hypothesise that the protective effect of DADLE on BMECs might be related to mitochondria.…”
Section: Open Accessmentioning
confidence: 99%
“…Transient receptor potential vanilloid 4 is a nonselective Ca 2+ -permeable cation channel that belongs to the transient receptor potential (TRP) subfamily [1,2]. The TRPV4 channel exhibits membranous expression and can be found in the brain, eyes, urinary system, gastrointestinal tract, skin, epithelial, vasculature, several musculoskeletal tissues, and innate immune system cells [2,3]. The TRPV4 ion channel activity is affected by changes in the cell membrane following heat, swelling, pH, mechanical, and biological stimuli [1,4].…”
Section: Introductionmentioning
confidence: 99%